A glossary of Targum Onkelos according to Alexander Sperber's edition - Cook, Edward M. (Studies in the Aramaic interpretation of Scripture, 2008)
Targum Onkelos is the oldest complete Jewish Aramaic translation of the Pentateuch, and it has played a major role in Jewish exegesis throughout the centuries. Although the vocabulary of Onkelos has been included in the major rabbinic dictionaries, there has never been a volume devoted solely to the vocabulary of Onkelos. This glossary, based on the standard critical edition, includes all of the vocabulary of the targum, plus geographical names, with bibliographical references to cognates in other Aramaic dialects. It will be a major help both to students first encountering the language of the Targum, as well as to specialists seeking a thorough treatment of its lexical features.